Searching for collisions between mobile robot and environment. (20th September 2016) - Hruboš, Marián; Svetlík, Jozef; Nikitin, Yury; Pirník, Rastislav; Nemec, Dušan; Šimák, Vojtech; Janota, Aleš; Hrbček, Jozef; Gregor, Michal
This article is focused on the search for potential collision of a moving object (as a mobile robot is) with the environment. Application of the proposed and presented method requires existence of the three-dimensional model of the environmental space. In this case, the models are generated automatically with the help of mobile measurement platform developed by authors and are available to other applications. Models of moving objects are loaded by the proposed application from external files. The method is based on data fusion, using data from a laser scanner, global positioning system, and inertial navigation system; however, it can also be used for data obtained by other ways. Its correctness was experimentally proved by several experimental tests. Output is in the form of calculated coordinates of the point in which a moving object would potentially collide with the environment if no avoiding action is taken. Such an object may represent an oversized load transferred by a truck, train, ship, the transport means itself or even a person.